(untitled) (Journal of the College of Basic Education, 2025)
This study aims to investigate the impact of industrial pollution on rainfall patterns by analyzing the relationship between emissions from industrial activities and climate changes. The research relies on a review of previous studies, climate data analysis, and climate modeling to understand how industrial pollution alters precipitation distribution. The findings indicate that industrial emissions, such as carbon dioxide (CO₂), nitrogen oxides (NOₓ), and fine particulate matter (PM2.5 and PM10), contribute to rising global temperatures, leading to disruptions in the hydrological cycle. Data show that major industrial areas experience higher-than-normal rainfall due to increased cloud formation, whereas some rural and remote areas suffer from decreased precipitation due to changes in wind patterns and air currents. The study also highlights that changes in rainfall patterns exacerbate extreme weather events, such as floods and droughts, posing environmental and economic challenges to affected communities. The research recommends implementing environmental measures to reduce industrial emissions, such as promoting clean energy use, enforcing strict environmental policies, and improving water resource management strategies to adapt to climate changes. It also calls for further studies to better understand the local and regional impacts of industrial pollution on climate